2020
DOI: 10.18001/trs.6.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Observed Circumvention of the Gutka Smokeless Tobacco Ban in Mumbai, India

Abstract: Objectives: Gutka is industrially manufactured in India and some Indian states have instituted bans on the sale of manufactured gutka as a public health initiative. We explored whether gutka was still available for purchase after the ban and also sought to observe methods of ban circumvention. Methods: We visited 5 different markets at different locations separated by at least 15-20 km around the Mumbai Metropolitan Region (MMR) area, consisting of Mumbai and its satellite towns in Maharashtra, India during A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…However, previous research has reported no change in the prevalence of chewing tobacco use in India between 1990 and 2019 8 . This contrasts with our findings, possibly because the Euromonitor data did not capture illegal sales of smokeless tobacco, which has been reported in India before 23 . This emphasizes the importance of considering sales and prevalence data together to obtain a more comprehensive understanding of tobacco use.…”
Section: Discussioncontrasting
confidence: 99%
“…However, previous research has reported no change in the prevalence of chewing tobacco use in India between 1990 and 2019 8 . This contrasts with our findings, possibly because the Euromonitor data did not capture illegal sales of smokeless tobacco, which has been reported in India before 23 . This emphasizes the importance of considering sales and prevalence data together to obtain a more comprehensive understanding of tobacco use.…”
Section: Discussioncontrasting
confidence: 99%
“…Rewards in the form of cash (n = 2) were also a motivating factor, which relate to two studies arguing that the effect of enforcement is stronger when officials are compensated by the fines collected [43,44]. Several barriers raised by the news are consistent with global and Indian tobacco control literature, particularly with regard to gutka, where legal loopholes, lack of awareness and enforcement, and litigation by tobacco industries are associated with violation of the ban, sale of twin packets, without mandated health warnings [31,45,46]. Only four reports mentioned the role of academia or NGOs, in…”
Section: Plos Global Public Healthmentioning
confidence: 67%
“…33,34 Many Indian states have banned the sale and advertising of Gutka (a common form of SLT) but a recent study asserts that it is readily available in Indian markets. 35 Carrying a fatalistic attitude towards health was identified as another major driving force for continuing SLT among our CAD patients. Previous studies have identified belief in fate as a hindrance to behavioural change.…”
Section: Discussionmentioning
confidence: 98%
“…33,34 Many Indian states have banned the sale and advertising of Gutka (a common form of SLT) but a recent study asserts that it is readily available in Indian markets. 35…”
Section: Discussionmentioning
confidence: 99%